Significance of myofibroblast appearance in squamous cell carcinoma of the oral cavity on the occurrence of occult regional metastases, distant metastases, and survival. Issue 9 (September 2015) - Luksic, I.; Suton, P.; Manojlovic, S.; Virag, M.; Petrovecki, M.; Macan, D.
Abstract The aim of the present study was to assess the frequency of appearance of stromal myofibroblasts in patients with oral squamous cell carcinoma (OSCC) and to further clarify whether myofibroblasts influence tumour suppression or progression. Surgical resection specimens from 152 patients with cT1–T3N0 OSCC were analysed. The frequency of myofibroblasts within the tumour stroma was assessed immunohistochemically and compared with other clinical and histopathological factors. The immunohistochemical reaction for alpha-smooth muscle actin showed positive cells in the stroma of 84.2% of OSCC (n = 128). An increased presence of myofibroblasts in the tumour stroma was significantly correlated with T stage (P = 0.019), the presence of occult neck metastasis (P < 0.001), regional recurrence (P = 0.037), and distant metastasis (P = 0.008). There was also an association between the presence of myofibroblasts and patient survival (P = 0.009). The presence of myofibroblasts was not associated with local recurrence, tumour cell differentiation, mode of invasion, or bone invasion. The results of this study suggest that myofibroblast proliferation facilitates tumour invasion, the occurrence of occult neck disease, and distant metastasis. The survival rate was poorer in patients with abundant myofibroblasts. Further investigations on tumour-associated stroma at the invasive front are needed in order to establish new diagnostic markers and therapeutic strategies.